Analysis Of Wearable Antenna Using Electromagnetic Band Gap Under Bending Conditions - Azmi, Aini Noor Liana (2018)
Wearable antenna caught many attentions among researchers due to its wide applications in the technology.The wearable antenna can be widely applied in military, medical,tracking,and many other fields due to its capability to function on the body and off the body.It is an advantage if the wearable antenna could operate with wide bandwidth.However,there are some drawbacks when designing wideband antenna.Backward radiation is one of the major drawbacks introduced by a wearable antenna. Therefore,it is crucial to reduce the backward radiation to avoid harm to the user.Hence,this thesis presents a wearable antenna integrated with Electromagnetic Band Gap (EBG) structure to perform at particular dual-band Wireless Local Area Network (WLAN) frequencies;2.4 GHz and 5.2 GHz.EBG structure is a type of metamaterial which cannot be found in nature.This structure has become one of the interests due to its extraordinary response to electromagnetic waves.The wearable antenna is designed in the form of circular ring microstrip patch antenna.Jeans have been used as the medium of the substrate.Jeans fabric is selected due to its high permittivity and inelasticity compared to the other materials.The overall size of the antenna is 70x70mm.In order to improve the performance of the antenna,an EBG is then designed to be integrated with the proposed wearable antenna.Next,the designed structures have been fabricated and measured for return loss,gain,directivity,and radiation pattern.The integration of the wearable antenna with the EBG structure has improved the overall performance.The gain of 5.711 dB and 7.474 dB has been achieved for both high and low resonating frequencies respectively,which shows almost 63.7% improvement at low frequency and 121.4% at high frequency.As the designed antenna is designed to be worn on the body,the bending effect of the structure is studied.Cylindrical foams are used to replace human torso for this purpose.Three radiuses have been selected, representing adult's wrist,arm,and thigh.The overall structure is then been tested under bending conditions; resulting intangible effect to the antenna's performances compared to the flat antenna.The return loss for the antenna was found to be very little affected by the presence of body which makes the designed antenna to be suitable for the wearable communication system.Thus,this antenna is suitable for WLAN application purposed especially for medical,consumer electronics sectors and military field.The details of the measured and simulated are presented and discussed.